Development of The American Society of Colon and Rectal Surgeons' Rectal Cancer Surgery Checklist. Issue 7 (July 2016) - Glasgow, Sean C.; Morris, Arden M.; Baxter, Nancy N.; Fleshman, James W.; Alavi, Karim S.; Luchtefeld, Martin A.; Monson, John R. T.; Chang, George J.; Temple, Larissa K.
Abstract : BACKGROUND: There is excellent evidence that surgical safety checklists contribute to decreased morbidity and mortality. OBJECTIVE: The purpose of this study was to develop a surgical checklist composed of the key phases of care for patients with rectal cancer. DESIGN: A consensus-oriented decision-making model involving iterative input from subject matter experts under the auspices of The American Society of Colon and Rectal Surgeons was designed. SETTINGS: The study was conducted through meetings and discussion to consensus. PATIENTS: Patient data were extracted from an initial literature review. MAIN OUTCOME MEASURES: The checklist was measured by its ability to improve care in complex rectal surgery cases by reducing the possibility of omission through the division of treatment into 3 distinct phases. RESULTS: The process generated a 25-item checklist covering the spectrum of care for patients with rectal cancer who were undergoing surgery. LIMITATIONS: The study was limited by its lack of prospective validation. CONCLUSIONS: The American Society of Colon and Rectal Surgeons rectal cancer surgery checklist is composed of the essential elements of preoperative, intraoperative, and postoperative care that must be addressed during the surgical treatment of patients with rectal cancer.